Searching for school dropouts (Praxis Educativa, 2015)
In Letters to a Professor, Barbiana students denounce school dropouts. At present, according to official registers, and due to the expanse of compulsory schooling, schools do not ‘lose’ students and astonishingly, high retention rates are publicized. But, regretfully, retention is not a synonym of learning and inclusion. Barbiana students foresaw danger when they realized that ‘students’ dropout rates’ led tragically to conclusive desertion. As teacher trainers, our academic and political responsibility compels us to deal with the problem and to suggest taking firm actions that contribute to the training of teachers truly devoted to the kind of education that enables a genuine inclusion, especially of those individuals who have historically been marginalized from schooling.
Keywords: compulsory schooling; retention; inclusion; teacher training